Optimized chronomodulated dual release bilayer tablets of fexofenadine and montelukast: quality by design, development, and in vitro evaluation - Bhupendra Singh; Geetanjali Saini; Manish Vyas; Surajpal Verma; Sourav Thakur (SpringerOpen, 2019)
Abstract Background The conventional oral dosage forms are not effective in dealing with chronopathological conditions, such as nocturnal asthma. Therefore, there is an unmet need to develop a delivery system that can deliver drug as per the chronopharmacology of the diseases. The purpose of the study is to use quality by design (QbD) technique and pulsatile principles for the development of Eudragit-coated dual release bilayer tablets. The dual layer consists of immediate release layer of fexofenadine HCl and sustained release layer of montelukast sodium. Results The quality target product profile of the formulation was developed, and the critical quality attributes were identified. Three-level, three-factor Box-Behnken design was used for the optimization of the bilayer tablets. Based on the design, a total of 13 formulation combinations (F1-F13 and M1-M13) were made having acceptable micromeritic properties. The developed immediate and sustained release layers were evaluated for physicochemical properties. Depending upon the value of the diffusion exponent, the Fickian diffusion mechanism is dominant among immediate and sustained release tablet layers. Response curve for immediate release layer showed that concentrations of sodium starch glycolate and sodium bicarbonate had a negative effect on disintegration time and a positive effect on drug release. For sustained release tablet layer, concentrations of HPMC E 5 LV and magnesium stearate had a significant effect on drug release. The ANOVA and diagnostic plots confirmed the significance and goodness of fit of the used model. Based on desirability plot values, optimized formulation was developed and coated with Eudragit coat. The coated bilayer tablet showed met the requirement of providing an immediate release during the first hour and a sustained release action for a period of more than 8 h after passing the gastric region. Conclusions The formulation can be fruitful in curbing the menace of nocturnal asthma and providing a high degree of patient compliance as the patient will not have to wake up at night to take the medication.